Assessment of glycemic control, health-related quality of life, and associated factors in type 2 diabetic patients attending a comprehensive specialized hospital in Northwest Ethiopia - Assefa Belay Asrie; Tafere Mulaw Belete; Melshew Fenta Misker; Alemante Tafese Beyna; Habtamu Semagne Ayele; Kidist Goshime Tekle; Yonas Zewdu Milikit; Ephrem Adane Andargie; Hiwot Tesfaselassie Afework; Yenatfanta Gezu Lenjiso; Gebrehiwot Lema Legese (PLoS ONE, 2025)
Background Poor glycemic control in type 2 diabetes mellitus (T2DM) leads to serious complications that negatively impact health-related quality of life (HRQoL). This study aimed to assess glycemic control, HRQoL, and their associated factors in T2DM patients. Method This is a cross-sectional study and was conducted from May 1 to July 30, 2024. Systematic random sampling technique was used to recruit the study participants. The average fasting blood glucose (FBG) levels of three consecutive tests during follow-up visits were extracted from patient medical records while the data pertaining HRQoL were collected through interview using EQ-5D five-level (EQ-5D-5L) questionnaire and EQ visual analog scale (EQ VAS). EQ-5D-5L utility scores were determined using disutility values established for Ethiopian context. The FBG level was used to categorize patients by glycemic status (controlled or uncontrolled). Binary logistic regression analysis was performed to outline factors associated with glycemic control. Mann–Whitney U and Kruskal–Wallis tests were used to compare the median utility and VAS scores between subgroups. Furthermore, Tobit regression analysis was performed to determine factors associated with HRQoL. Results Nearly half (48.7%) of the patients were with uncontrolled glycemic levels (out of the target 4.4−72 mmol/L). In the multivariate logistic regression analysis, age, disease duration, comorbid conditions, diabetes complications, adherence to antidiabetic medications, and herbal medicine use were associated with glycemic control. Pain/discomfort, performing usual activities, and anxiety/depression were HRQoL dimensions in which the majority of participants reported problems; 85.8%, 76.2%, and 74.6% of participants, respectively, reported having problems in the dimensions. The overall median (interquartile range) EQ-5D-5L utility score was 0.86 (0.76–0.93) while EQ VAS score was 75.0 (65.0–80.0). The Tobit regression analysis showed that older age, diabetes duration, comorbid conditions, diabetic complications, and herbal medicine use were significantly negatively associated with HRQoL scores. On the other hand, engagement in physical exercise, controlled glycemic level, and adherence to antidiabetic treatments were found to be positively associated. Conclusion In conclusion, nearly half of the patients were with uncontrolled glycemic level. The majority of participants reported problems in pain/discomfort, usual activities, and anxiety/depression dimensions of HRQoL. Several factors were correlated with both glycemic control and HRQoL. Adherence to antidiabetic medications was positively associated with both glycemic control and HRQoL. In contrast, older age, longer duration of diabetes, presence of comorbidities, diabetic complications, and use of herbal medicine were all negatively associated with both outcomes. On the other hand, adherence to dietary recommendations was positively associated only with glycemic control, while engagement in physical exercise was positively associated only with HRQoL. Moreover, glycemic control was associated with improved HRQoL. The findings underscore the importance of interventions targeting modifiable factors, such as dietary modifications, physical activity, and adherence support, to improve overall glycemic control and HRQoL.